Paleolithic artifact deposits at Wadi Dabsa, Saudi Arabia: A multiscalar geoarchaeological approach to building an interpretative framework. Issue 3 (28th January 2019) - Inglis, Robyn H.; Fanning, Patricia C.; Stone, Abi; Barfod, Dan N.; Sinclair, Anthony; Chang, Hsing‐Chung; Alsharekh, Abdullah M.; Bailey, Geoff
Abstract: Surface artifacts dominate the archaeological record of arid landscapes, particularly the Saharo‐Arabian belt, a pivotal region in dispersals out of Africa. Discarded by hominins, these artifacts are key to understanding past landscape use and dispersals, yet behavioral interpretation of present‐day artifact distributions cannot be carried out without understanding how geomorphological processes have controlled, and continue to control, artifact preservation, exposure and visibility at multiple scales. We employ a geoarchaeological approach to unraveling the formation of a surface assemblage of 2, 970 Palaeolithic and later lithic artifacts at Wadi Dabsa, Saudi Arabia, the richest locality recorded to date in the southwestern Red Sea coastal region. Wadi Dabsa basin, within the volcanic Harrat Al Birk, contains extensive tufa deposits formed during wetter conditions. We employ regional landscape mapping and automatic classification of surface conditions using satellite imagery, field observations, local landform mapping, archaeological survey, excavation, and sedimentological analyses to develop a multiscalar model of landscape evolution and geomorphological controls acting on artifact distributions in the basin. The main artifact assemblage is identified as a palimpsest of activity, actively forming on a deflating surface, a model with significant implications for future study and interpretation of this, and other, surface artifact assemblages.